Peran Kepemimpinan Kepala Ruangant erhadap Pencegahan Risiko Jatuh dalam Keselamatan Pasien di Rumah Sakit - Indriaty, Julia; Kusumapradja, Rokiah; Wahidi, Kemala Rita (Lembaga Penerbitan Universitas Esa Unggul, 2021)
Background: The high number of patients falling for a year in a hospital is a serious problem in the hospital because the incidence of falling patients is one indicator of patient safety. The purpose of this study was to analyze the application of falling risk prevention management and training on the implementation of patient safety with the leadership role of the head of the room as an intervening variable. The research uses quantitative research methods with survey methods with questionnaires and Structural Equation Model (SEM) analysis methods, Amos version 23. Research samples of nurses who have received patient safety training are 178 nurses. From the results of testing the model has met the Goodness of fit criteria. The results of this study indicate that the risk reduction prevention management variable has a positive effect on patient safety, training has a positive effect on patient safety management. The implementation of falling risk management has a positive effect on the leadership role of the head of room, training has a positive effect on patient safety management, training has a positive effect on risk management the leadership role of the head of the room has a positive effect on patient safety. The direct coefficient of patient risk falls on patient safety is greater than the indirect coefficient shows there is an indirect effect of the patient's risk of falling on the implementation of patient safety through the leadership role of the head of the room. the direct coefficient of training on patient safety is greater than the indirect coefficient indicating there is an indirect effect of patient safety training on the implementation of patient safety through the leadership role of the head of the room. and the lack of optimal training obtained by the head of the room resulted in his leadership role not being optimally performed. The management of RSUD Cengkareng in this case was providing a budget, and giving the head of the room the opportunity to take part in training that could support the leadership of the head of the room.Keywords: Management of Risk Prevention of Falling, Training, Implementation of Patient Safety, Role of Leadership of Room Heads